2020
DOI: 10.1016/j.jml.2020.104172
|View full text |Cite
|
Sign up to set email alerts
|

Immediate sensorimotor grounding of novel concepts learned from language alone

Abstract: Note: This is the author's preprint version of the article (date: 17. 08. 2020). The final article is accepted for publication in the Journal of Memory and Language. Theories of grounded cognition postulate that concepts are grounded in sensorimotor experience. But how can that be for concepts like Atlantis for which we do not have that experience? We claim that such concepts obtain their sensorimotor grounding indirectly, via already-known concepts used to describe them. Participants learned novel words refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 54 publications
3
30
0
1
Order By: Relevance
“…The findings reviewed above are consistent with the suggestion that distributional models that take only language data as input may be adequate for broadly capturing semantic similarity, and emerging evidence suggests that novel words may, to some degree, acquire embodied representations by virtue of the embodied properties of the contexts in which they appear (Günther et al, 2020;Snefjella et al, 2020; see also Snefjella & Kuperman, 2016). An interesting open question is whether embodied experience alone (e.g., Öttl et al, 2017) also facilitates category learning, or whether language is necessary for carving categorical boundaries into our experience (for review, see Lupyan, 2012).…”
Section: Effects Of Embodied and Distributional Linguistic Informatiosupporting
confidence: 76%
See 3 more Smart Citations
“…The findings reviewed above are consistent with the suggestion that distributional models that take only language data as input may be adequate for broadly capturing semantic similarity, and emerging evidence suggests that novel words may, to some degree, acquire embodied representations by virtue of the embodied properties of the contexts in which they appear (Günther et al, 2020;Snefjella et al, 2020; see also Snefjella & Kuperman, 2016). An interesting open question is whether embodied experience alone (e.g., Öttl et al, 2017) also facilitates category learning, or whether language is necessary for carving categorical boundaries into our experience (for review, see Lupyan, 2012).…”
Section: Effects Of Embodied and Distributional Linguistic Informatiosupporting
confidence: 76%
“…As described above, it has been proposed that we can learn embodied meanings of words through acquired embodiment (e.g., Hoffman et al, 2018), whereby sensory-perceptual properties can be attributed to, for example, more abstract concepts by virtue of them sharing linguistic contexts with concrete concepts, (e.g., a relatively abstract concept like death might become associated with black via associations with funeral). And indeed, novel words can acquire embodied-like representations from purely linguistic experience (Günther et al, 2020). Specifically, after novel words were learned in contexts implying upwards or downwards movements, action-congruency effects were found if participants had to access word meaning.…”
Section: Effects Of Embodied and Distributional Linguistic Informatiomentioning
confidence: 99%
See 2 more Smart Citations
“…Fernandino et al (2013) studied the ACE in patients suffering from Parkinson's disease, a disorder in the functioning of the motor system, and found that such patients were slower to understand sentences that describe an action than healthy subjects. Günther et al (2020) showed that an effect similar to the ACE occurred also with novel concepts describing actions, which had been grounded in sensorimotor experience.…”
Section: Introductionmentioning
confidence: 94%